A Case of Submandibular Leiomyosarcoma, Mimicking an Abscess, in a Ball Python (Python regius) - Jun Kwon; Sang Wha Kim; Sang Guen Kim; Hyoun Joong Kim; Sung Bin Lee; Jeong Woo Kang; Won Joon Jung; Sib Sankar Giri; Kyunglee Lee; Se Chang Park (Veterinary Sciences, 2021)
A two-year-old ball python with a submandibular mass was evaluated. Fine needle aspiration resulted in debris containing purulent materials and bacterial cells on cytology. Radiography demonstrated multi-focal radiopaque lesions in the mass, which were suspected to be mineralization; there was an absence of mandibular invasion or lung involvement. Gross examination of the surgically excised mass revealed a multi-nodular, well-circumscribed lesion with purulent material. The postoperative recovery was uneventful. The histopathological examination followed by immunohistochemistry analysis gave a diagnosis of leiomyosarcoma. As tumors containing purulent materials can be confused with an abscess, diagnostic confirmation with various diagnostical tools should be considered.